Peroxydisulfate-assisted sonocatalytic degradation of metribuzin by La-doped ZnFe layered double hydroxide - Akdag, Sultan; Rad, Tannaz Sadeghi; Keyikoglu, Ramazan; Orooji, Yasin; Yoon, Yeojoon; Khataee, Alireza (Elsevier, 2022)
Metribuzin is an herbicide that easily contaminates ground and surface water. Herein, La-doped ZnFe layered double hydroxide (LDH) was synthesized for the first time and used for the degradation of metribuzin via ultrasonic (US) assisted peroxydisulfate (PDS) activation. The synthesized LDH had a lamellar structure, an average thickness of 26 nm, and showed mesoporous characteristics, including specific surface area 110.93 m(2) g(-1), pore volume 0.27 cm(3) g(-1), and pore diameter 9.67 nm. The degradation efficiency of the US/La-doped ZnFe LDH/PDS process (79.1 %) was much greater than those of the sole processes, and the synergy factor was calculated as 3.73. The impact of the reactive species on the sonocatalytic process was evaluated using different scavengers. After four consecutive cycles, 10.8 % loss occurred in the sonocatalytic activity of the La-doped LDH. Moreover, the efficiency of the US/La-doped LDH/PDS process was studied with respect to the degradation of metribuzin in a wastewater matrix. According to GC-MS analysis, six by-products were detected during the degradation of metribuzin. Our results indicate that the US/La-doped ZnFe LDH/PDS process has great potential for efficient degradation of metribuzin-contaminated water and wastewater.
Keywords: Herbicide degradation; Hydrotalcite; Peroxydisulfate activation; Ultrasound process; Water treatment